Penstabilan Suhu Pengeringan Kopi dengan Kontrol Logika Fuzzy - Rangga Al Arif (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2021)
Conventional method of drying coffee by drying in direct sunlight has a disadvantage, namely the unpredictable environmental temperature, to get optimal grain drying results, a drying machine with a rotary system is made, coffee stabilization is also very important during the drying process, temperature fluctuating fluctuations will affect the grain drying results, therefore a set point of 40oC is set, because if the set point is less than 40oC the microbes that cause decay are still alive, and if the temperature is more than 40oC then only the outer skin of the coffee will dry, to maintain stability. temperature during the drying process, a fuzzy logic control is used. The right fuzzy membership value is used, the fuzzy control is connected to the DHT11 temperature sensor and the SG90 servo actuator, after testing, the fuzzy logic control with 5 membership functions is the right value, the drying process coffee gets kada r water of 14.1% with a drying rate of 1.17%.